Butuanon Cuisine: In Search of Local Identity - Lerida, Manolita R.; Garay, Apolonia V. (JPAIR Multidisciplinary Research, 2010)
As evidenced by the ancient traders, Butuan is known for its valuable resources like the value of Butuanon food plants such as lumbia trunk upon which kinabo (winnowed unaw flour), palagsing (boiled unaw flour), inisab (hot mixed unaw flour) and tinumpi (pressed heated unaw flour) are made. The Butuanons cooked their food utilizing their ethnic cooking styles, revealing the Butuanon's Identity through their food preparation. The study used the ethno-historical method through the oral interview with the aid of an interview schedule. The interviews were cross-checked through the different key informants from the six villages, with a total of thirty-six (36) key informants. The originality and authenticity of the Butuanon Cuisine and recipes in the six villages Banza, Bobon, Libertad, Doongan, Maug and Babag can be traced back to the ancient period, which continued during the Spanish and American periods up to the present. The continuity of the Butuan food preparation survived due to the demands of the old Butuanons and the existence of the supply of the native food resources.
Keywords: Butuanon cuisine (bulbous); Indigenous Filipino food; Sago (Lumbia) based dishes